A comprehensive study on the effects of truncation positions of the compound parabolic concentrator eliminating multiple reflections on the performances of concentrating photovoltaic and thermal system. (25th January 2021) - Zhang, Gaoming; Wei, Jinjia; Zhang, Liang; Xi, Chengsi; Ding, Rui; Wang, Zexin; Khalid, Muhammad
Highlights: Effect of truncation position of EMR on performance of CPV/T system was studied. Energy and exergy efficiencies of CPV/T system with EMR were evaluated. The EMR with height of 543 mm showed the highest energy and exergy efficiencies. Total energy and exergy efficiencies of CPV/T system could reach 73.68% and 15.86%. Overall exergy efficiency of CPV/T system was 1.67% higher than that of PV system. Abstract: In the present study, we intend to carry out a comprehensive study on the effects of truncation positions of a new-type truncated compound parabolic concentrator (CPC) on the performances of concentrating photovoltaic and thermal (CPV/T) systems regarding optical performance of the concentrator, temperature distribution of PV, energy and exergy efficiencies of the CPV/T systems. This new-type truncated CPC was designed by means of eliminating multiple reflections (EMR) in our previous work. Thus we called it EMR concentrator. To implement our objective, firstly, analytical equation group was established to design EMR concentrators with various truncation positions. Secondly, ray tracing of EMR concentrators was conducted by TracePro. The optical efficiency and irradiance distribution of EMR concentrators were analyzed. Thirdly, temperature distribution of PV, energy and exergy efficiencies of CPV/T systems were predicted by a two-dimensional electrical-thermal coupled model. Finally, performances of CPV/T system were compared with those of PV system. Results showed that optical efficiency of EMR concentrators is increasing with a decrease in truncation position due to increasing number of diffuse rays collected by the receiver directly, but irradiance and PV temperature distribution exhibit some difference. Irradiance and PV temperature non-uniformity increases slightly with a drop in truncation position firstly and then decreases slightly. As EMR concentrator is further truncated and the concentrator height is less than 543 mm, irradiance and PV temperature non-uniformity increases rapidly with a drop in truncation position. Furthermore, variations in electrical, thermal and total energy efficiencies display a reversed trend to variations in irradiance and PV temperature non-uniformity. As for exergy efficiency, electrical and overall exergy efficiencies show the same trend as energy efficiencies. However, thermal exergy efficiency exhibits little variation due to a low Carnot efficiency of thermal energy. From the energy and exergy point of view, EMR concentrator with height of 543 mm shows the best performance compared to other EMR concentrators. When it's applied to CPV/T system, the electrical, thermal and total energy efficiencies are 12.45%, 61.23% and 73.68% respectively. The overall exergy efficiency can achieve 15.86%. A comparison between CPV/T and PV systems shows that though electrical efficiency of CPV/T system is 1.74% lower than that of PV system, PV temperature is 16.5 ℃ lower than that of PV system. Moreover, a remarkable thermal output makes the overall exergy efficiency of CPV/T system is 1.67% higher than that of PV system.